A mAb for the detection of the antiretroviral drug emtricitabine. (1st November 2022) - Youngpairoj, Ae S.; Vanderford, Thomas H.; Reed, Matthew S.; Granade, Timothy C.; Pau, Chou-Pong; Pohl, Jan; Switzer, William M.; Heneine, Walid
Abstract : Antibody-based testing for emtricitabine (FTC), a critical component of pre-exposure prophylaxis and antiretroviral therapy, would provide low-cost detection for clinical monitoring to improve adherence. We developed a mAb (5D2) to FTC and demonstrated its high specificity and physiologically relevant linear range of detection in a competitive enzyme immunoassay. Thus, this mAb is a key reagent that will enable simple and low-cost lateral flow assays and enzyme immunoassays for adherence monitoring.